TISSUE AROMA TERAPI "UPIK ABU" (UNTUK PENYELAMAT BUMI KITA TERBUAT DARI AMPAS TEBU) - Fauziah, Nuraini; Istikhomah, Novita; Andriyan, Exwan; Puspawati, Andina (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
Abstract Entrepreneurship Student Creativity Program of "Upik Abu" Tissue (made from sugar cane dregs to save the earth) is in response to the increasing need for tissues. It is also motivated by the intention to produce tissues without cutting down trees as an effort to save the environment, as well as to use of the cane pulp which is usually only used as fuel for locomotives. This program is aimed to: (1) produce Aroma Therapy Tissue, (2) develop a marketing strategy, and (3) get the sales profit. This activity includes producing tissues through a cooperation with partners, introducing, and selling products of "Upik Abu" tissues. The implementation stage includes the activities of market surveys and production. The market survey is conducted to get an overview of market potencial. The production process consists of three stages, namely preparation, execution, and finishing. The tissues are produced in the form of facial tissues, toilet tissues, and tissues at the dinner table. The process of marketing is done through printed media (business cards, leaflets, mass media), electronic media (facebook, twitter, blogs, SMS), community, exhibition, and consignment with some grocery stores. Aroma therapy is added to the tissue to be more marketable as well as comfortable to use. Tissue production has reached 650 units, with sales profit for three months of 3,862,500 rupiahs. Based on the results obtained it can be concluded that the business is profitable, so the continuity of business will continue to be maintained, along with the efforts to increase profits.